IoT-driven environmental optimization for hydroponic lettuce: A data-centric approach to smart agriculture - BARUS, Okky Putra; MAULANA, Ade; YUGOPUSPITO, Pujianto; HIDAYANTO, Achmad Nizar; ALEXANDER, Winar Joko (Applied Computer Science, 2025)
An IoT sensor network enables real-time monitoring of key environmental parameters, including temperature, humidity, nutrient solution pH, and concentration. This system employs a rule-based expert system with dynamic threshold adjustments for automated control. Over a 35-day growth cycle (Days After Transplanting - DAT), the experiment revealed statistically significant improvement in lettuce growth within the smart indoor farming system compared to outdoor farming. Average increases were observed: 17.1% in plant weight, 16.9% in plant height, and 20.0% in the number of leaves. The IoT-based control system robustly maintained environmental parameters within optimal ranges, creating a stable and conducive growth environment. This approach highlights the transformative potential of integrating IoT and intelligent control logic for optimizing indoor hydroponic crop production, paving the way for more efficient and sustainable agriculture. The findings offer insights for future smart farming developments by demonstrating how IoT and intelligent control improve hydroponic lettuce yield.